Massive intraperitoneal free air induced by pneumothorax and pneumomediastinum. (2018) - Fujiwara, Kei; Ohsaka, Hiromichi; Nagasawa, Hiroki; Takeuchi, Ikuto; Jitsuiki, Kei; Kondo, Akihiko; Omori, Kazuhiko; Ishikawa, Kouhei; Yanagawa, Youichi
Highlights: Intraperitoneal free air can be induced by pneumothorax and pneumomediastinum. This is the massive intraperitoneal free air by pneumothorax and pneumomediastinum. Air dissects its way downwards along the esophagus and aorta into the retroperitoneal tissues. Deterioration of traumatic pneumothorax and/or occurrence of pneumomediastinum after mechanically ventilation is the most considerable reason of the PP in the present case. Abstract: Introduction: Pneumoperitoneum (PP), or air within the abdominal cavity, is frequently a harbinger of serious abdominal pathology and often represents visceral perforation. We herein report a case of combined massive intraperitoneal free air, pneumothorax and pneumomediastinum but emergency laparotomy was negative. Presentation of case: A sixty-seven-year-old man was found unconscious on a road after being hit by a car. On arrival, he showed swelling of the head and flail chest. Computed tomography (CT) demonstrated cerebral contusion, multiple bilateral rib fractures, minute subcutaneous emphysema and a left hemothorax. As his consciousness and respiratory function deteriorated, tracheal intubation with mechanical ventilation with positive end-expiratory pressure was executed on the second day. On the third day, the CT scan revealed the new appearance of pneumomediastinum and massive free air in his intraperitoneal space. Emergency laparotomy was negative. Discussion: The 'air leak' phenomenon, in which an alveolar air cell ruptures into the perivascular and peribronchial interstitial tissues, is a well-recognized consequence of positive end-expiratory pressure therapy. Accordingly, the deterioration of traumatic pneumothorax and/or the occurrence of pneumomediastinum after mechanical ventilation was the most likely cause of the PP in the present case. However, it remains possible that a minute unrecognized diaphragmatic injury caused the massive PP in the present case. Conclusion: We herein described a case of PP that occurred after mechanical ventilation in a patient with multiple injuries, but which did not originate from perforation of the gastrointestinal tract. It is most likely that the PP had an intrathoracic cause.